ANALISIS PERBANDINGAN PENGUJIAN LENTUR BALOK TAMPANG PERSEGI SECARA EKSPERIMENTAL DI LABORATORIUM DENGAN PROGRAM RESPONSE 2000 - Amir, Fatmawati (MEKTEK, 2010)
General, rectangular beam construct to take flexural and shear force. Flexural test can visualitation in thelaboratorium if there are tools like loading frame, load cell, hydraulic jack and data logger. This researchgive alternative conclusion for flexural test used Response-2000 programme, beside the test result.Response-2000 was one programme used to analyse beam and column with combination load cause axialforce, moment and shear force. This method can used to know the behavior of rectangular beam based onlayer method and produce load-bending response, shear force, axial load, moment-curvature, and strainmomentdiagram to know ductility and strength of beam